2019
DOI: 10.1097/meg.0000000000001637
|View full text |Cite
|
Sign up to set email alerts
|

Add-on sorafenib is beneficial for hepatocellular carcinoma patients with transarterial chemoembolization refractoriness: a real-world experience

Abstract: Background and aims: Sorafenib is the first proved target therapy that shows significant survival benefit in advanced hepatocellular carcinoma. This study was aimed to investigate whether add-on sorafenib be beneficial for those experienced transarterial chemoembolization refractoriness. Methods: From 2005 to 2016, a total of 656 treatment-naive hepatocellular carcinoma patients receiving transarterial chemoembolization treatment were recruited. Transar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The inconsistent conclusions may be because the study by Yang et al explicitly confines the inclusion criteria to unresectable HCC patients, whereas others did not stipulate this limitation and had fewer analysed subjects. Similarly, two retrospective studies [52,53] also reported a favourable OS in the combination group as compared to TACE alone.…”
Section: Discussionmentioning
confidence: 78%
“…The inconsistent conclusions may be because the study by Yang et al explicitly confines the inclusion criteria to unresectable HCC patients, whereas others did not stipulate this limitation and had fewer analysed subjects. Similarly, two retrospective studies [52,53] also reported a favourable OS in the combination group as compared to TACE alone.…”
Section: Discussionmentioning
confidence: 78%
“…This study found that 39.6% of patients had AEs, but no patients had AEs of grade III or higher. Meanwhile, camrelizumab had a lower incidence of AEs in HCC patients with UP after TACE compared with sorafenib [23,33]. Unlike nivolumab and pembrolizumab, RCCEP is more common after camrelizumab treatment [34].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, when TACE acts as a curative treatment, the outcome of SD or progressive disease is identified as TACE failure/refractoriness. Currently, the concept of TACE failure/refractoriness has been widely introduced, especially in clinical trials for HCC[ 5 , 9 , 10 , 15 , 16 ]. However, these concepts require further discussion due to low evidence-based data.…”
Section: Review Of Different Definitions Of Tace Failure/refractorinessmentioning
confidence: 99%
“…In addition, Yttrium-90 radioembolization and Iodine-125 ( 125 I) seed brachytherapy have been adopted to control target lesions[ 29 - 31 ]. TACE combined with systemic therapy or loco-regional therapy revealed favorable outcomes and good tolerance[ 15 , 31 , 32 ].…”
Section: Comprehensive Analyses Of the Endpoints For Tace In Tace Fai...mentioning
confidence: 99%